2019
DOI: 10.1161/hypertensionaha.119.12998
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA–DACH1 (Dachshund Homolog 1) Regulates Cardiac Function by Inhibiting SERCA2a (Sarcoplasmic Reticulum Calcium ATPase 2a)

Abstract: Heart failure (HF) is a major cause of morbidity and mortality in patients with various cardiovascular diseases. Restoration of cardiac function is critical in improving the clinical outcomes of patients with HF. Long noncoding RNAs are widely involved in the development of multiple cardiac diseases, whereas their role in regulating cardiac function remains unclear. In this study, we found that the expression of long noncoding RNA–DACH1 (dachshund homolog 1) was upregulated in the failing hearts of mice and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…Currently, the treatment of osteoporosis is currently mainly aimed at osteoclasts ( Ensrud and Crandall, 2017 ; Roux and Briot, 2018 ), and the new therapy with teriparatide has shown a more curative effect in osteoporosis ( Minisola et al, 2019 ), which suggests that treatment options directed at osteoblasts are of great significance. Adenoviruses containing lncRNAs were used to treat mice and showed a significant therapeutic effect in many diseases, including ischemic myocardial injury ( Cai et al, 2019 ) and cardiac regeneration ( Ponnusamy et al, 2019 ). To clarify the possible role of Gas5 in osteoporosis treatment, we supplemented Gas5 -overexpressing adenoviruses in an osteoporosis mouse model based on the preceding results.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the treatment of osteoporosis is currently mainly aimed at osteoclasts ( Ensrud and Crandall, 2017 ; Roux and Briot, 2018 ), and the new therapy with teriparatide has shown a more curative effect in osteoporosis ( Minisola et al, 2019 ), which suggests that treatment options directed at osteoblasts are of great significance. Adenoviruses containing lncRNAs were used to treat mice and showed a significant therapeutic effect in many diseases, including ischemic myocardial injury ( Cai et al, 2019 ) and cardiac regeneration ( Ponnusamy et al, 2019 ). To clarify the possible role of Gas5 in osteoporosis treatment, we supplemented Gas5 -overexpressing adenoviruses in an osteoporosis mouse model based on the preceding results.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA refers to a non-coding RNA of base compositions ranging from 200 nt to 100000 nt NA, and it plays an important role in the biological processes such as cell cycle regulation, epigenetic inheritance regulation, transcription regulation and post-transcription regulation etc., and it is involved in a series of diseases in nervous system, cardiovascular system and malignant tumor etc.. [13][14][15][16] With the deepening of research, it is found that, more and more LncRNA are closely related to the generation and development of brain glioma. [17,18] LINC00152 refers to a member of LncRNA family, and it has abnormal expression at malignant tumors such as liver cancer, gastric cancer and colon cancer etc.. [19,20] The latest clinical studies have shown that, LINC00152 is associated with poor clinical prognosis of brain glioma.…”
Section: Discussionmentioning
confidence: 99%
“…36,47,59,60 Conditional knockout of Lnc-DACH or overexpression Lnc-TINCR resulted in increasing calcium transient, and improving cardiac function after transverse aortic constriction in mice. 41 Inhibition of Lnc-Chaer expression before the onset of pressure overload substantially attenuates cardiac hypertrophy on mouse model. 26…”
Section: Ln Crna : a P Otential Targ E T For C Ardiac Hypertrophymentioning
confidence: 99%